2019
DOI: 10.1136/bmjopen-2018-028434
|View full text |Cite
|
Sign up to set email alerts
|

Communicative characteristics of general practitioner-led and nurse-led telephone triage at two Danish out-of-hours services: an observational study of 200 recorded calls

Abstract: ObjectivesOut-of-hours (OOH) telephone triage is used to manage patient flow, but knowledge of the communicative skills of telephone triagists is limited. The aims of this study were to compare communicative parameters in general practitioner (GP)-led and nurse-led OOH telephone triage and to discuss differences in relation to patient-centred communication and safety issues.DesignObservational study.SettingTwo Danish OOH settings: a large-scale general practitioner cooperative in the Central Denmark Region (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The emotional feeling of worry is a catalyst for help-seeking, however, this is rarely touched upon in telephone triage [17,46]. A Danish study of 200 audio-recorded telephone triage conversations found that callers were invited to express their emotional state in less than 2% of the calls [10]. In an analysis of malpractice claim cases the authors found that a failure to respond to the callers' concern, closed biomedical questions and less information sharing characterized malpractice claims in cases compared to matched controls [15,16,47].…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The emotional feeling of worry is a catalyst for help-seeking, however, this is rarely touched upon in telephone triage [17,46]. A Danish study of 200 audio-recorded telephone triage conversations found that callers were invited to express their emotional state in less than 2% of the calls [10]. In an analysis of malpractice claim cases the authors found that a failure to respond to the callers' concern, closed biomedical questions and less information sharing characterized malpractice claims in cases compared to matched controls [15,16,47].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Triage tools are recommended to aid health care professionals' decision making [6], but these tools generally perform well only in the low and high levels of urgency, but less so in the middle triage categories [6,7], moreover, they are criticized for not incorporating the patient's context and perception nearly enough [8,9]. In a Danish study from 2019 based on 200 calls to a medical helpline, researchers found that less than 2% of the callers were invited to express their emotional state [10]. Therefore, a need exists for a tool that systematically incorporates the patient's perception of the situation and symptoms in telephone triage.…”
Section: Introductionmentioning
confidence: 99%
“…The nurse starts this phase by asking an open and nonspeci c question to invite the caller to tell their story (2,(25)(26)(27). The caller usually presents their reason for calling as a narrative (26) and prefers to tell the story at the beginning of the call (47). It is important that the caller be allowed to tell their story in full without being interrupted by questions or unnecessary remarks (38,42,(47)(48).…”
Section: Inviting the Caller To Tell Their Storymentioning
confidence: 99%
“…The caller is given time and space to speak (28,31,36,40,47). The nurse is active and responsive in listening and encourages the full telling of the caller's story (38,52).…”
Section: Inviting the Caller To Tell Their Storymentioning
confidence: 99%
“…This was supported in a substudy involving 200 of the calls included in this study that nurses allowed the patient to speak uninterrupted in the beginning for significantly longer time than GPs (GP median spontaneous talking time: 17.9 s vs nurse: 23.4 s). 28 Previous findings that have found CDSS use constraining and explores mostly medical information. 26 27 Moreover, indicators of efficiency could influence the patient-centredness of the communication negatively.…”
mentioning
confidence: 99%